Serum and urine galactose deficient-IgA1 as alternative biomarkers in the management of IgA nephropathy - Suleman-alabi, Aminat; Abd Ghani, Fauzah; Zakaria, Nor Fadhlina; Hod, Rafidah (Malaysian Medical Association, 2024)
Introduction: Immunoglobulin A (IgA) nephropathy (IgAN) results from abnormal accumulation of immune complexes containing galactose deficient IgA1 (Gd-IgA1) in the kidneys. About 40% of patients develop end-stage kidney disease within 20 years of renal biopsy. At present, the diagnosis and risk stratification of patients (using the international IgAN risk prediction tool) rely on renal biopsy, which is an invasive procedure. Also, treatment decisions are still dependent on proteinuria, which is not specific for IgA nephropathy. We discussed the role of serum and urine Gd-IgA1 in the diagnosis of IgAN, its association with disease progression and changes with treatment in patients with IgA nephropathy. Materials and Methods: A systematic search of PubMed and Scopus databases was done to identify the articles that are relevant to the topic including systematic reviews and original articles. Results: Several studies showed that both serum and urine Gd-IgA1 differentiate IgA nephropathy patients from healthy people and other glomerulonephropathies. Thus, it is useful as a less invasive diagnostic biomarker, although detection methods varied between studies with different sensitivities. There are various reports of its use as a prognostic parameter. Evidence is emerging for its use as a monitoring parameter for treatment. Conclusion: Galactose deficient IgA1 is a promising biomarker in the management of IgA nephropathy, although a more robust and standardised means of estimation is required.